2013
DOI: 10.3109/15412555.2012.752806
|View full text |Cite
|
Sign up to set email alerts
|

Airway Dimensions in Fatal Asthma and Fatal COPD: Overlap in Older Patients

Abstract: In some patients with chronic asthma clinical and physiological similarities with COPD may exist, such as partial reversibility to bronchodilators and persistent expiratory airflow obstruction. However, pathological data comparing both diseases in patients of similar age and disease severity are scarce. We compared large and small airway dimensions in 12 younger (mean age 32 yrs) and 15 older (mean age 65 yrs) non-smoker adult fatal asthma patients with 14 chronic smokers with severe, fatal COPD (mean age 71 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…This may contribute to airflow reduction independent of airway remodeling, a characteristic feature of asthma in patients of all ages. Studies of small and large airway wall area and thickness in older versus younger individuals with asthma have shown conflicting results by computed tomography (CT) scans and autopsy assessments (44,45). It is likely that aging alone does not lead to airway remodeling; however, longer duration of asthma may lead to increased airway narrowing due to progressive remodeling and increase in airway smooth muscle volume (45).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may contribute to airflow reduction independent of airway remodeling, a characteristic feature of asthma in patients of all ages. Studies of small and large airway wall area and thickness in older versus younger individuals with asthma have shown conflicting results by computed tomography (CT) scans and autopsy assessments (44,45). It is likely that aging alone does not lead to airway remodeling; however, longer duration of asthma may lead to increased airway narrowing due to progressive remodeling and increase in airway smooth muscle volume (45).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Studies of small and large airway wall area and thickness in older versus younger individuals with asthma have shown conflicting results by computed tomography (CT) scans and autopsy assessments (44,45). It is likely that aging alone does not lead to airway remodeling; however, longer duration of asthma may lead to increased airway narrowing due to progressive remodeling and increase in airway smooth muscle volume (45). Thus, factors attributable to asthma alone, combined with those due to normal aging, may account for the accelerated decline in FEV 1 in asthma noted longitudinally in some large population studies (46,47).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…The technique involves endoscopic application of thermal radiofrequency energy to ablate underlying smooth muscle altering airway structure. It has been shown that structural changes in the older fatal asthmatic share overlapping features with those of younger fatalities (58) . This suggests that bronchial thermoplasty may be of benefit in a selected subset of older patients with asthma.…”
Section: Bronchial Thermoplastymentioning
confidence: 99%
“…12,13 The outer wall of small membranous bronchioles was the main site of inflammatory changes in patients with fatal asthma. 12,13 Recently, Senhorini et al 18 noted younger adults with fatal asthma had thicker basement membrane, smooth muscle, and outer wall areas in both the small and large airways when compared with both patients with COPD and older asthmatic patients. In older asthmatic patients there was an overlap in basement membrane thickness and airway structure in the small airways.…”
mentioning
confidence: 99%